Analysis of clinical characteristics, treatment response, and prognosis among 67 patients with anaplastic multiple myeloma - Fei Chen; Yan Wang; Zhongxia Huang; Man Qi; Hong Chen (World Journal of Surgical Oncology)
Abstract Background Anaplastic multiple myeloma (AMM) is a type of distinctive MM with a poor prognosis. AMM is mostly reported as individual cases, an accurate incidence and strict clinical definition are lacking. Methods Sixty-seven patients with AMM were identified and then analyzed in the clinical database of patients with MM from January 2017 to September 2024. Results The incidence of AMM among patients with MM was 3.3%. The IgD type accounted for 11.9% of patients, with 40.3% and 53.7% kappa and lambda light chains, respectively. Plasmablasts with larger diameters and multinuclear variations accounted for 46.7% from bone marrow or extramedullary disease (EMD) based on pathologic morphology; the average Ki-67 was 64.8%. The incidence of EMD was 49.3%. Lactic dehydrogenase (LDH) was elevated in 44.8% of patients and 49.3% of patients were International Staging System (ISS) III. The frequencies of 1q21, t (4; 14), and t (14; 16) in high-risk genes were 60.5%, 39.5%, and 18.4%, respectively. Double and triple gene hits were detected in 36.8% and 13.2% of patients, respectively. Fifty-six patients received treatment with bortezomib-based regimens. The progression-free survival (PFS) and overall survival (OS) of AMM patients in the autologous stem cell transplantation (ASCT) group were prolonged compared to patients who did not undergo ASCT with a median PFS and OS of 5.0 versus 25.0 and 17.0 versus 36.0 months, respectively (P = 0.0246 and P = 0.0119, respectively). At the time of the last follow-up, 71.4% of patients had died with 77.5% experiencing disease progression. A high neutrophil-to-lymphocyte ratio (NLR) and no ASCT were also independent prognostic factors for AMM patients. Conclusions The incidence of AMM is rare. The characteristics of these AMM patients included extensive proliferation of plasmablasts and widespread EMD formation, AMM patients also exhibit more invasive clinical manifestations and a short survival. Patients who underwent sequential ASCT after receiving bortezomib-based regimens partially overcame the poor prognosis of AMM.